Exogenous peptides are able to penetrate human cell and mitochondrial membranes, stabilize mitochondrial tRNA structures, and rescue severe mitochondrial defects. Issue 6 (18th April 2020) - Perli, Elena; Pisano, Annalinda; Pignataro, Maria Gemma; Campese, Antonio Francesco; Pelullo, Maria; Genovese, Ilaria; de Turris, Valeria; Ghelli, Anna Maria; Cerbelli, Bruna; Giordano, Carla; Colotti, Gianni; Morea, Veronica; et al.
Abstract: Mutations in mitochondrial transfer RNA (mt‐tRNA) genes are responsible for a wide range of syndromes, for which no effective treatment is available. We previously reported that transfection of the nucleotide sequence encoding for the 16‐residue β32_33 peptide from mitochondrial leucyl‐tRNA synthetase ameliorates the cell phenotype caused by the mitochondrial tRNA mutations. In this work, we demonstrated that both the β32_33 peptide linked with the known (L)‐Phe‐(D)‐Arg‐(L)‐Phe‐(L)‐Lys (FrFK) mitochondrial penetrating sequence and, strikingly, the β32_33 peptide per se, are able to penetrate both the plasma and mitochondrial membranes and exert the rescuing activity when exogenously administered to cells bearing the mutations m.3243A > G and m.8344A > G. These mutations are responsible for the most common and severe mt‐tRNA‐related diseases. In addition, we dissected the molecular determinants of constructs activity by showing that both the order of amino acids along the sequence and presence of positive charges are essential determinants of the peptide activity in cells and mt‐tRNA structures stabilization in vitro. In view of future in vivo studies, this information may be required to design of β32_33 peptide‐mimetic derivatives. The β32_33 and FrFK‐β32_33 peptides are, therefore, promising molecules for the development of therapeutic agents against diseases caused by the mt‐tRNA point mutations.